Foreign exchange volatility modeling of Southeast Asian major economies - Regi Muzio Ponziani (Journal of Economics, Business, and Accountancy Ventura, 2019)
This study investigates the exchange rate volatility model in Southeast Asian countries. The countries selected were Indonesia, Malaysia, Thailand, The Philippines, Vietnam, and Singapore. This study aims to model the volatility of the regional currency exchange rate against the international currency, i.e., the US Dollar. The period covered in this study extended from 1 January 2013 until 31 July 2019. These were the daily exchange rates of 7 currencies of Southeast Asian countries. The currency involved were Indonesian Rupiah (IDR), Malaysian Ringgit (MYR), Thai Baht (THB), The Philippine Peso (PHP), Vietnam Dong (VND), and Singaporean Dollar (SGD). All currencies were measured in the exchange rate against the US Dollar (USD). The result indicated that PARCH model is the best method to explain the movement of MYR, VND, and SGD. GARCH can model THB and PHP. Only IDR that has volatility explainable by TARCH.